The Effect of Complex Exercises on Some Motor Abilities and Enduring the Skillful Performance of Football Players - Atiyah Mohammed, Makram; Fadaws Omar, Adnan (International Journal of Psychosocial Rehabilitation, 2020)
This method of training, which includes complex exercises, has an important and significant impact on developing the capabilities of the teams that use it in all aspects, the most important of which is the skill side, as global teams attach great importance to this type of training, feeling that it is one of the ways and means that contribute to raising the physical and skill capabilities of the players.The aim of the research was1. players. Learn about the effect of complex (physical-skill) exercises on some of the motor abilities of youth football2. Knowing the effect of combined (physical-skill) exercises on bearing the skillful performance of youth football players.The researchers used the experimental approach to its relevance and nature of research. As for the research sample, it was determined from Al-Adhamiya Sports Club for youth football (17-19 years) and officially registered in the statements of the Iraqi Central Football Association for the current season (2018-2019), and the number (34) player was chosen in the intentional way. After that, 26 players were chosen from them; two goalkeepers, one injured player, and five players were excluded from the piloting experience. The researcher selected Al-Adhamiya Sports Club as a sample to search in an intentional way.Through what was collected from the results and after statistically processing, the most important conclusions were reached, as follows:1. It was found that there were statistically significant differences for the pre- and posttests of the experimental and control groups and the motor abilities and bearing the skill performance in favor of the posttest.2. The combined exercises (physical and skill) that were used in the training method obtained the objectives that were set for the development of research variables.